Effectiveness of case management interventions for frequent users of healthcare services: a scoping review - Catherine Hudon; Maud-Christine Chouinard; Isabelle Dufour; Mireille Lambert; Cynthia Krieg (BMJ Open)
Objective Frequent users of healthcare services are a vulnerable population, often socioeconomically disadvantaged, who can present multiple chronic conditions as well as mental health problems. Case management (CM) is the most frequently performed intervention to reduce healthcare use and cost. This study aimed to examine the evidence of the effectiveness of CM interventions for frequent users of healthcare services.Design Scoping review.Data sources An electronic literature search was conducted using the MEDLINE, Scopus and CINAHL databases covering January 2004 to December 2015. A specific search strategy was developed for each database using keywords ‘case management’ and ‘frequent use’.Eligibility criteria for selecting studies To be included in the review, studies had to report effects of a CM intervention on healthcare use and cost or patient outcomes. Eligible designs included randomised and non-randomised controlled trials and controlled and non-controlled before–after studies. Studies limited to specific groups of patients or targeting a single disease were excluded. Three reviewers screened abstracts, screened each full-text article and extracted data, and discrepancies were resolved by consensus.Results The final review included 11 articles evaluating the effectiveness of CM interventions among frequent users of healthcare services. Two non-randomised controlled studies and 4 before–after studies reported positives outcomes on healthcare use or cost. Two randomised controlled trials, 2 before–after studies and 1 non-randomised controlled study presented mitigated results. Patient outcomes such as drug and alcohol use, health locus of control, patient satisfaction and psychological functioning were evaluated in 3 studies, but no change was reported.Conclusions Many studies suggest that CM could reduce emergency department visits and hospitalisations as well as cost. However, pragmatic randomised controlled trials of adequate power that recruit the most frequent users of healthcare services are still needed to clearly confirm its effectiveness.